Evaluation of ground-based methods for monitoring neotectonic processes at geodynamic sites - B. Lysko; T. Hutsul (Екологічна безпека та збалансоване ресурсокористування)
The relevance of the article lies in the need to improve the methods of monitoring neotectonic processes and develop technological parameters to ensure more effective forecasting of geodynamic phenomena. Accurate monitoring of neotectonic processes is important for assessing changes in geological conditions and preventing potential risks affecting the environment and human life safety. The purpose of research was to evaluate the effectiveness of various ground-based methods of monitoring neotectonic processes to determine their reliability and accuracy. The authors used different methods, in particular geodetic measurements, which ensure high accuracy and reliability of the results; geophysical methods that help to detect subsurface structures and processes; and remote sensing of the Earth, which provides large-scale monitoring and analysis of the dynamics of neotectonic phenomena. Having analysed the existing methods of determining the changes in the shape of the equipotential surface, the advantages of using geodetic measurements to ensure the accuracy and reliability of the measurement results were identified and substantiated. The proposed methodology is based on the study of changes in the shape of the equipotential surface on geotechnological sites and takes into account the inhomogeneity of the gravity field, and if the developed technological parameters are followed, it ensures the determination of the deflection of plumb lines with an accuracy of ± 0.2". The research results showed that the combination of these methods helps to obtain a more complex picture of neotectonic processes, which, in turn, contributes to more accurate forecasting and prevention of the consequences of geodynamic phenomena. The proposed approach to monitoring neotectonic processes can be used to develop effective strategies for monitoring and managing environmental risks associated with geological hazards